Regulation of Notch signaling in the developing Drosophila eye by a T‐box containing transcription factor, Dorsocross. Issue 10 (12th November 2018) - Paul, Maimuna S.; Dutta, Debdeep; Singh, Ankita; Mutsuddi, Mousumi; Mukherjee, Ashim
Summary: Owing to a multitude of functions, there is barely a tissue or a cellular process that is not being regulated by Notch signaling. To allow the Notch signal to be deployed in numerous contexts, many different mechanisms have evolved to regulate the level, duration and spatial distribution of Notch activity. To identify novel effectors of Notch signaling in Drosophila melanogaster, we analyzed the whole transcriptome of the wing and eye imaginal discs in which an activated form of Notch was overexpressed. Selected candidate genes from the transcriptome analysis were subjected to genetic interaction experiments with Notch pathway components. Among the candidate genes, T‐box encoding gene, Dorsocross ( Doc ) showed strong genetic interaction with Notch ligand, Delta . Genetic interaction between them resulted in reduction of eye size, loss of cone cells, and cell death, which represent prominent Notch loss of function phenotypes. Immunocytochemical analysis in Df(3L)DocA/Dl 5f trans‐heterozygous eye discs showed accumulation of Notch at the membrane. This accumulation led to decreased Notch signaling activity as we found downregulation of Atonal, a Notch target and reduction in the rate of Notch‐mediated cell proliferation. Doc mutant clones generated by FLP‐FRT system showed depletion in the expression of Delta and subsequent reduction in the Notch signaling activity. Similarly, Doc overexpression in the eye discs led to modification of Delta expression, loss of Atonal expression and absence of eye structure in pharate adults. Taken together, our results suggest that Doc regulates the expression of Delta and influence the outcome of Notch signaling in the eye discs.